Peningkatan Kapasitas Usaha Mina Mandiri Melalui Pelatihan Pemasaran Produk Olahan Ikan - Amalia Nadifta Ulfa; Umi Barokah; Darsono Darsono; Rhina Uchyani Fajarningsih; Joko Sutrisno; Suprapti Supardi (PRIMA: Journal of Community Empowering and Services, 2020)
Title:Capacity Building for Mina Mandiri Business Through Marketing Training of Fish Processed ProductsThe income earned from the main job as a rice farmer has not been able to meet the needs of a farmer family in Sindumartani Village, Ngemplak, Sleman. Residents use some of the land for tilapia farming. Tilapia aquaculture business has not provided significant additional revenue. Farmers market fresh fish with simple techniques (conventional) with a limited scope. Mina Mandiri Fish Farmers Group is required to be more creative in setting marketing strategies so that their products are better known, interested in consumers and reach a wider market. Farmer groups need marketing training to increase their business capacity. Market efforts by combining offline strategies and online strategies. This service is carried out in order to provide marketing training. The existence of this marketing training provides the right marketing knowledge for fish processed products, so that it can increase the marketing area and increase the group's business capacity.